Geo-Congress 2014 Technical Papers 2014
DOI: 10.1061/9780784413272.171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pile Size on Set-Up Behavior of Cohesive Soils

Abstract: Driven piles usually experience significant increase in axial load resistance over time, known as set-up. A large portion of this set-up can be completed within the first few hours, and can also take a few days to months for set-up to complete. Dynamic and static load tests are usually performed to verify the axial resistances of piles at specific times after end of driving (EOD) and to quantify these resistances. The pile driving and testing records of 45 square precast prestressed piles (PPC) of various size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…; Q@ xwqa "CU= VQ}o QDt=Q=B w l=N C=}YwYN u=}t |x]@= Q 'QwmPt VywSB QO QDt=Q=B u=W}= '1988 5 QwvO w wmU= \UwD xOW x=Q= |x]@= Q uDiQo Q_vQO =@ 'u}= |iQat l=N C=}YwYN R= |a@=D u=wvax@ = Q xOW xQ=W= |x]@= Q QO A VQ}o [12] "Ov=xOQm QF= |UQQ@ u=wva =@ 2014 Q}N= u= QoWywSB R= |Qo}O xHwD p@=k VywSB u; QO xm 'OQ=O OwHw x]@=Q u}= QO xOv@UJ |=yl=N QO VQ}o u= R}t QO `tW O=a@= |=v=}R}}wr Cr=}= QO xO}vDV}B w xDN=UV}B |vD@ `tW 45 V@ wm G}=Dv |=yxO=O R= QF= |UQQ@ |= Q@ Iv}= 30 w 24 '16 '14 O=a@= =@ =y`tW R= xwQo 4 w xO=iDU= =m} Qt; Q}N= VywSB G}=Dv "Ov=xOW ?=NDv= l=N u=Um} \}=QW CLD 'VQ}o QO `tW O=a@= CU= umtt xO}OB u}= "O@=}|t V}=Ri= R}v VQ}o MQv '`tW O=a@= V}=Ri= =@ xm O=O u=Wv =Hx@=H = Q l=N R= |QDW}@ sHL 'QDnQR@ O=a@= =@ |}=y`tW xm OyO |wQ Cra u}= x@ lqyDU= xm OwW|t O=H}= |QDW}@ |}xQiL ? ; Q=Wi xi=[= xH}Dv QO w Ovvm|t |=y`tW x@ C@Uv nQR@ |=y`tW h= Q]= l=N QO |QDW}@ Ctw=kt Ov=wD|t u; xDU@=w |Q@Q=@ C}iQ_ |v}@V}B |= Q@ |irDNt |=yVwQ [13]…”
mentioning
confidence: 99%
“…; Q@ xwqa "CU= VQ}o QDt=Q=B w l=N C=}YwYN u=}t |x]@= Q 'QwmPt VywSB QO QDt=Q=B u=W}= '1988 5 QwvO w wmU= \UwD xOW x=Q= |x]@= Q uDiQo Q_vQO =@ 'u}= |iQat l=N C=}YwYN R= |a@=D u=wvax@ = Q xOW xQ=W= |x]@= Q QO A VQ}o [12] "Ov=xOQm QF= |UQQ@ u=wva =@ 2014 Q}N= u= QoWywSB R= |Qo}O xHwD p@=k VywSB u; QO xm 'OQ=O OwHw x]@=Q u}= QO xOv@UJ |=yl=N QO VQ}o u= R}t QO `tW O=a@= |=v=}R}}wr Cr=}= QO xO}vDV}B w xDN=UV}B |vD@ `tW 45 V@ wm G}=Dv |=yxO=O R= QF= |UQQ@ |= Q@ Iv}= 30 w 24 '16 '14 O=a@= =@ =y`tW R= xwQo 4 w xO=iDU= =m} Qt; Q}N= VywSB G}=Dv "Ov=xOW ?=NDv= l=N u=Um} \}=QW CLD 'VQ}o QO `tW O=a@= CU= umtt xO}OB u}= "O@=}|t V}=Ri= R}v VQ}o MQv '`tW O=a@= V}=Ri= =@ xm O=O u=Wv =Hx@=H = Q l=N R= |QDW}@ sHL 'QDnQR@ O=a@= =@ |}=y`tW xm OyO |wQ Cra u}= x@ lqyDU= xm OwW|t O=H}= |QDW}@ |}xQiL ? ; Q=Wi xi=[= xH}Dv QO w Ovvm|t |=y`tW x@ C@Uv nQR@ |=y`tW h= Q]= l=N QO |QDW}@ Ctw=kt Ov=wD|t u; xDU@=w |Q@Q=@ C}iQ_ |v}@V}B |= Q@ |irDNt |=yVwQ [13]…”
mentioning
confidence: 99%
“…The parameter A can be assumed, backcalculated from field data, or gleaned from empirical relationships available in the literature. Published literature has shown that the parameter A is a function of soil type and properties, and pile type and size (1,3,10,11). A few studies have described the effects of soil properties on the magnitude or rate of setup and incorporated soil properties in the setup prediction model.…”
mentioning
confidence: 99%